Informational Frictions and the Credit Crunch - DARMOUNI, OLIVIER (Journal of Finance, 2020)
ABSTRACT In this paper, I estimate the magnitude of an informational friction limiting credit reallocation to firms during the 2007 to 2009 financial crisis. Because lenders rely on private information when deciding which relationship to end, borrowers looking for a new lender are adversely selected. I show how to separately identify private information from information common to all lenders but unobservable to the econometrician by using bank shocks within a discrete choice model of relationships. Quantitatively, these informational frictions appear to be too small to explain the credit crunch in the U.S. syndicated corporate loan market.